Efficacy and safety profile of elexacaftor-tezacaftor-ivacaftor triple therapy on cystic fibrosis: a systematic review and single arm meta-analysis - Xu, Wenye; Wu, Ting; Zhou, Zijing; Zuo, Zhihong (Frontiers in Pharmacology, 2023)
Background: Elexacaftor-Tezacaftor-Ivacaftor (ELE/TEZ/IVA) is believed to be an effective and well-tolerated treatment for cystic fibrosis (CF), but the exact efficacy and safety profile are still unknown.Objective: This study aimed to clarify the extent of functional restoration when patients are given with triple combination treatment and demonstrate the prevalence of adverse events, to evaluate the overall profile of ELE/TEZ/IVA on CF. Methods: A literature search was conducted in PubMed, Web of Science and Cochrane Library. Random effects single-arm meta-analysis was performed to decipher the basal characteristics of CF, the improvement and safety profile after ELE/TEZ/IVA treatment. Results: A total 53 studies were included in this analysis. For all the patients in included studies. 4 weeks after ELE/TEZ/IVA treatment, the increasement of percentage of predicted Forced Expiratory Volume in the first second (ppFEV1) was 9.23% (95%CI, 7.77%-10.70%), the change of percentage of predicted Forced Vital Capacity (ppFVC) was 7.67% (95%CI, 2.15%-13.20%), and the absolute change of Cystic Fibrosis Questionnaire-Revised (CFQ-R) score was 21.46 points (95%CI, 18.26-24.67 points). The Sweat chloride (SwCl) was significantly decreased with the absolute change of -41.82mmol/L (95%CI, -44.38 to -39.25mmol/L). 24 weeks after treatment, the increasement of ppFEV1 was 12.57% (95%CI, 11.24%-13.90%), the increasement of ppFVC was 10.44% (95%CI, 7.26%-13.63%), and the absolute change of CFQ-R score was 19.29 points (95%CI, 17.19-21.39 points). The SwCl was significantly decreased with the absolute change of -51.53mmol/L (95%CI, -56.12 to -46.94 mmol/L). The lung clearance index2.5 (LCI2.5) was also decreased by 1.74 units (95%CI, -2.42 to -1.07 units). The body mass index increased by 1.23kg/m 2 (95%CI, 0.89-1.57 kg/m 2 ). As for adverse events, 0.824 (95%CI, 0.769-0.879) occurred during ELE/TEZ/IVA period, while the incidence of severe adverse events was 0.066 (95%CI, 0.028-0.104). Conclusion: ELE/TEZ/IVA is a highly effective strategy and relatively safe for CF patients and needs to be sustained to achieve better efficacy.